Cutaneous Electrohydraulic (CUTE) Wearable Devices for Pleasant Broad‐Bandwidth Haptic Cues - Natalia Sanchez‐Tamayo; Zachary Yoder; Philipp Rothemund; Giulia Ballardini; Christoph Keplinger; Katherine J. Kuchenbecker (Advanced Science)
Abstract By focusing on vibrations, current wearable haptic devices underutilize the skin's perceptual capabilities. Devices that provide richer haptic stimuli, including contact feedback and/or variable pressure, are typically heavy and bulky due to the underlying actuator technology and the low sensitivity of hairy skin, which covers most of the body. This article presents a system architecture for compact wearable devices that deliver salient and pleasant broad‐bandwidth haptic cues: Cutaneous Electrohydraulic (CUTE) devices combine a custom materials design for soft haptic electrohydraulic actuators that feature high stroke, high force, and electrical safety with a comfortable mounting strategy that places the actuator in a non‐contact resting position. A prototypical wrist‐wearable CUTE device produces rich tactile sensations by making and breaking contact with the skin (2.44 mm actuation stroke), applying high controllable forces (exceeding 2.3 N), and delivering vibrations at a wide range of amplitudes and frequencies (0–200 Hz). A perceptual study with 14 participants achieves 97.9% recognition accuracy across six diverse cues and verifies their pleasant and expressive feel. This system architecture for wearable devices gives unprecedented control over the haptic cues delivered to the skin, providing an elegant and discreet way to activate the user's sense of touch.